Green skills at industrial training institutes in India : an exploratory study of VET teachers’ subjective theories - Albertz, Annabell [Verfasser]; Pilz, Matthias [Verfasser] (My University, 2025)
“This study addresses the subjective theories of vocational education and training (VET) teachers on green skills, as their understanding and attitude towards phenomena can influence teaching, students and institutions on a large scale. Specifically, the study focuses on Indian teachers at Industrial Training Institutes (ITIs), as these institutions are the main providers of formal vocational training in India. Despite the increasing demand in India for a workforce equipped with green skills, research on this subject, particularly from the perspective of VET teachers, remains limited. To address this gap, semi-structured interviews were conducted with 54 teachers across 19 ITIs in New Delhi and Bangalore. The findings reveal a diverse spectrum of teachers’ subjective theories on green skills, ranging from a lack of understanding, through a simple and pragmatic approach with environmentally friendly activities, to a technical approach, and finally to a broader view involving green moral values. Teachers’ attitudes towards green skills in vocational training are more favourable when they perceive a direct link between green skills and technical skills in their trade. The study is of both scientific and practical relevance, as investigating teachers’ subjective theories is crucial for further development in teacher training, continuing education and VET curricula in India and beyond.“ (authors’ abstract; BIBB-Doku)
Keywords: P 3.2.3 Lehrer; 370; Berufsschullehrer; Bildungspersonal; Green skills / Grüne Kompetenzen; Einstellung; Subjektive Theorien; Indien